Blended Learning Design and Green Shipping Technology Integration in Maritime Vocational Officer Education - Tri Kismantoro; Tri Cahyadi; Winarno (PT. Global Research Collaboration, 2026)
Global decarbonization pressures and technological disruption in maritime industries create urgent demand for deck and engine officers possessing both traditional operational competencies and contemporary green technology expertise. This research examined how blended learning designs combining simulator based instruction, theoretical instruction, and hands on practical training effectively integrate green shipping competencies such as alternative fuel propulsion, environmental compliance, and IMO 2050 carbon reduction into vocational maritime officer education. A mixed methods quasi experimental design compared learning outcomes between blended learning groups consisting of simulator, theory, and practical instruction and traditional instruction control groups across four maritime institutions (n = 184 students). Results demonstrated significant advantages for blended learning on green technology competency assessment and knowledge transfer measures. Instructor technological pedagogical content knowledge significantly predicted student outcomes, highlighting the importance of teacher capacity development. Thematic analysis of faculty interviews with step by step open and focused coding revealed that institutional barriers such as simulator equipment costs, faculty technological pedagogical knowledge limitations, and curriculum time constraints substantially limited green technology integration despite widespread recognition of its importance. Representative participant quotations illustrate the experiential texture of these barriers and enablers. The study contributes an empirically validated blended learning framework for maritime green technology education that positions simulator based experiential learning within an experiential learning cycle framework, advances technological pedagogical integration in maritime vocational contexts, and provides evidence based guidance for institutions navigating the pedagogical and resource tensions of decarbonization era officer education.